Avaliacao das condicoes de saude bucal dos idosos em um municipio brasileiro - Correa da Silva, S. R. [UNESP]; Valsecki Júnior, Aylton [UNESP] (FapUNIFESP (SciELO), 2000)
This study assessed the oral health of individuals 60 years or older in the city of Araraquara, Sao Paulo, Brazil, in 1998. Of the 194 people who participated in the study, 91 of them were institutionalized and had an average age of 73.6 years, and 103 were not institutionalized and had an average age of 69.3 years. The study participants were examined by a previously trained oral surgeon who determined the prevalence of the most common oral health problems. The results revealed a large number of edentulous individuals (72% of those institutionalized and 60% of the noninstitutionalized participants) and many persons with extracted teeth (93% and 90%, respectively), as well as a high frequency of periodontal pockets (57% and 75%, respectively) and of inadequate dentures (80% and 61%, respectively). Our results show reduced quality of life for a large proportion of these older individuals, and also indicate that public health services should pay greater attention to this population group.
Assessment of oral health in an elderly Brazilian population
Keywords: adult; aged; Brazil; dental health; elderly care; human; institutional care; major clinical study; oral surgery; periodontal disease; periodontitis; prevalence; public health service; quality of life; tooth extraction; dental care; female; health; health care delivery; health survey; male; middle aged; mouth disease; nursing home; statistics; tooth prosthesis; urban population; Aged; Aged, 80 and over; Dental Care for Aged; Dental Health Surveys; Dental Prosthesis; DMF Index; Female; Health Services Accessibility; Humans; Male; Middle Aged; Mouth Diseases; Nursing Homes; Oral Health; Prevalence; Urban Population